Identification of compound causing yellow bone discoloration following alpha-glycosyl isoquercitrin exposure in Sprague–Dawley rats - Davis, Jeffrey P. (Arch Toxicol, 2020)
Previous rat toxicity studies of alpha-glycosyl isoquercitrin (AGIQ), a water-soluble flavonol glycoside derived from rutin, revealed systemic yellow bone discoloration. This investigative study was conducted to determine the AGIQ metabolite(s) responsible for the discoloration. Female Sprague–Dawley rats were administered dietary AGIQ at doses of 0%, 1.5%, 3.0%, or 5.0% (0, 1735.0, 3480.8, and 5873.7 mg/kg/day, respectively) for 14 days, followed by a 14- or 28-day recovery period. Measurements of quercetin in urine and quercetin, quercetin 3-O-glucuronide, kaempferol, and 3-o-methylquercetin metabolites of AGIQ in bone (femur), white and brown fat, and cerebrum samples were conducted following the exposure period and each recovery period. Gross examination of the femur revealed yellow discoloration that increased in intensity with dose and was still present in a dose-related manner following both recovery periods. Quercetin, at levels correlating with AGIQ dose, was measured in the urine following the 14-day exposure period and, at lower concentrations, 14 or 28 days following cessation of AGIQ exposure. All four metabolites were present in a dose-dependent manner in the femur following 14 days of dietary exposure; only quercetin, quercetin 3-O-glucuronide, and 3-o-methylquercetin were present during the recovery periods. Quercetin, quercetin 3-O-glucuronide, and 3-o-methylquercetin were detected in white fat (along with kaempferol), brown fat (excluding quercetin due to analytical interference), and cerebrum samples, indicating systemic availability of the metabolites. Collectively, these data implicate quercetin, quercetin 3-O-glucuronide, or 3-o-methylquercetin (or a combination thereof) as the most likely metabolite of AGIQ causing the yellow discoloration of bone in rats administered dietary AGIQ.